Development of PDF Flipbook as Muhadatsah Learning Media for Students - Shilla Rahmi -; Kholisin; Moh Fauzan (Al-Lisan: Jurnal Bahasa)
Innovation in educational media is crucial for enhancing students' interest and motivation, especially in Arabic language learning. The use of technology-based media is an appropriate choice because it aligns with the current advancements in students' learning environments. One such example is the Flipbook PDF. This research and development project aims to create a Flipbook PDF as a medium for muhadatsah learning and to describe the feasibility of the developed media. The method used is Research and Development with the ADDIE model, which includes five stages of development: analysis, design, development, implementation, and evaluation. The development results in an online-based Flipbook PDF accessible via a link. This Flipbook features 3 chapters aligned with the Kemenag curriculum for Arabic language learning in the second semester of Grade VIII. Each chapter includes vocabulary and examples of muhadatsah with audio, instructional videos, muhadatsah videos, and practice exercises. The material validation results show a score of 89.3%, and the media validation results show a score of 90.6%, both categorized as valid. Meanwhile, the media feasibility test on the subjects shows a score of 79%, categorized as fairly feasible. Therefore, it can be concluded that the Flipbook PDF is proven to be a suitable medium for muhadatsah learning for Grade VIII MTs students.